2021
DOI: 10.3390/f12121627
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Identification and Expression Profiling of SPX Domain-Containing Members in Responses to Phosphorus Deprivation of Pinus massoniana

Abstract: The SPX domain-encoding proteins are believed to play important roles in phosphorus (Pi) homeostasis and signal transduction in plants. However, the overall information and responses of SPXs to phosphorus deficiency in pines, remain undefined. In this study, we screened the transcriptome data of Pinus massoniana in response to phosphorus deprivation. Ten SPX domain-containing genes were identified. Based on the conserved domains, the P. massoniana SPX genes were divided into four different subfamilies: SPX, SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Moreover, SPX1 , SPX3 , and SPX5 were up-regulated under P deficiency and N+P deficiency ( Figure S5 ). Studies have shown that most SPX subfamily members are induced by Pi deficiency in plants ( Stefanovic et al., 2007 ; Zhang et al., 2016 ; Du et al., 2017 ; Wang et al., 2021a ), and their major role is to interact with PHR1, thereby regulating the transcription of downstream PSIs ( Lv et al., 2014 ; Dong et al., 2019 ). Furthermore, PHO1 was down-regulated under three treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SPX1 , SPX3 , and SPX5 were up-regulated under P deficiency and N+P deficiency ( Figure S5 ). Studies have shown that most SPX subfamily members are induced by Pi deficiency in plants ( Stefanovic et al., 2007 ; Zhang et al., 2016 ; Du et al., 2017 ; Wang et al., 2021a ), and their major role is to interact with PHR1, thereby regulating the transcription of downstream PSIs ( Lv et al., 2014 ; Dong et al., 2019 ). Furthermore, PHO1 was down-regulated under three treatments.…”
Section: Discussionmentioning
confidence: 99%